Future faith : ten challenges reshaping Christianity in the 21st century - Granberg-Michaelson, Wesley (Word & world books., 2018)
In Future Faith: Ten Challenges Reshaping the Practice of Christianity, author Wesley Granberg-Michaelson provides a lucid view of how the top ten winds of change blowing through global Christian faith are reshaping the practice of Christianity today. He is uniquely qualified to identify and interpret connection points between global Christian trends and the American church. Drawing on the stories, examples, and personalities of pastors and congregations from throughout the U.S. as well as those from Africa, Asia, Latin America, who are the faces of Christianity's future, Future Faith is designed to inform and empower followers of Jesus to seek new ways of becoming the face of Christ to a rapidly changing world. Leaders and practitioners in church growth, renewal, and planting will be a primary audience for this book. Students of religion from Catholic, evangelical, Pentecostal, and historic Protestant streams will find this book an informative and stimulating resource for pondering together the future of their faith. Small groups engaged in congregational nurture and growth will find in the author a welcome companion for guiding them through the multi-cultural landscape of contemporary faith.